A Gay Century 10 Unreliable Vignettes of Lesbian and Gay Life. - Scott-Presland, Peter (Scott-Presland, Peter. Gay Century, 2021)
'A Gay Century: Vol 1' is a canter through 60 years of gay history in ten serious or comic playlets._x000D__x000D_Wilde's deathbed encounter with Queen Victoria; the theft of the Irish crown jewels by a sadomasochistic cabal in Dublin Castle; Compton Mackenzie demanding of the Home Secretary that his own lesbian novel be prosecuted like 'The Well of Loneliness', because he needs the money; matinee idol Ivor Novello sharing a cell in Wandsworth with teenage psycho 'Mad' Frankie Fraser; the Jeremy Thorpe/Norman Scott affair seen through the eyes of the dogs involved, etc. etc.